ASP.NET Core 2 and Angular 5 : full-stack web development with .NET Core and Angular - De Sanctis, Valerio (Packt Publishing, 2017)
Develop a simple, yet fully-functional modern web application using ASP.NET Core MVC, Entity Framework and Angular 5. About This Book Based on the best-selling book ASP.NET Core and Angular 2 Easily build a complete single page application with two of the most impressive frameworks in modern development, ASP.NET Core and Angular Bring together the capabilities and features of both Angular 5 and ASP.NET Core 2 for full stack development Discover a comprehensive approach to building your next web project-From managing data, to application design, through to SEO optimization and security Who This Book Is For This book is for seasoned ASP.NET developers who already know about ASP.NET Core and Angular in general, but want to know more about them and/or understand how to blend them together to craft a production-ready SPA. What You Will Learn Use ASP.NET Core to its full extent to create a versatile backend layer based on RESTful APIs Consume backend APIs with the brand new Angular 5 HttpClient and use RxJS Observers to feed the frontend UI asynchronously Implement an authentication and authorization layer using ASP.NET Identity to support user login with integrated and third-party OAuth 2 providers Configure a web application in order to accept user-defined data and persist it into the database using server-side APIs Secure your application against threats and vulnerabilities in a time efficient way Connect different aspects of the ASP. NET Core framework ecosystem and make them interact with each other for a Full-Stack web development experience In Detail Become fluent in both frontend and backend web development by combining the impressive capabilities of ASP.NET Core 2 and Angular 5 from project setup right through the deployment phase. Full-stack web development means being able to work on both the frontend and backend portions of an application. The frontend is the part that users will see or interact with, while the backend is the underlying engine, that handles the logical flow: server configuration, data storage and retrieval, database interactions, user authentication, and more. Use the ASP.NET Core MVC framework to implement the backend with API calls and server-side routing. Learn how to put the frontend together using top-notch Angular 5 features such as two-way binding, Observables, and Dependency Injection, build the Data Model with Entity Framework Core, style the frontend with CSS/LESS for a responsive and mobile-friendly UI, handle ...